2020
DOI: 10.1101/2020.10.13.20211854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent symptoms after Covid-19: qualitative study of 114 “long Covid” patients and draft quality criteria for services

Abstract: Background Approximately 10% of patients with Covid-19 experience symptoms beyond 3-4 weeks. Patients call this long Covid. We sought to document the lived experience of such patients, their accounts of accessing and receiving healthcare, and their ideas for improving services. Method We held 55 individual interviews and 8 focus groups (n = 59) with people recruited from UK-based long Covid patient support groups, social media and snowballing. We restricted some focus groups to health professionals since they… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 36 publications
(53 reference statements)
4
61
2
Order By: Relevance
“…Previous research involving people with long COVID has reported a substantial impact on identity. 10 11 Our study extends these findings; people for whom PA was a core aspect of their identity pre-COVID-19 were more inclined to push themselves physically, willing to risk relapses or view them as constructive. Their mental health was also more contingent on being able to undertake PA. PA identity has previously been associated with commitment, ability and self-regulation, with research suggesting that identity–behaviour discrepant situations can create negative affect.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous research involving people with long COVID has reported a substantial impact on identity. 10 11 Our study extends these findings; people for whom PA was a core aspect of their identity pre-COVID-19 were more inclined to push themselves physically, willing to risk relapses or view them as constructive. Their mental health was also more contingent on being able to undertake PA. PA identity has previously been associated with commitment, ability and self-regulation, with research suggesting that identity–behaviour discrepant situations can create negative affect.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings illustrate the impact of long COVID on the energy reserves of individuals, which is consistent with previous reports. 10 11 Our study highlights the importance of activities of daily living (ADLs (eg, housework, gardening) and outdoor activity to the normality and mental health of people with long COVID interviewed. ADLs have been defined as fundamental skills required for independent living 25 and are often used to assess physical function.…”
Section: Discussionmentioning
confidence: 76%
“…1 2 Frequent symptoms that were reported are fatigue, impaired physical and cognitive function, headache, breathlessness, palpitations and many other symptoms, impairing activities of daily living in many patients. [3][4][5][6][7] A recent publication of a patient survey of long COVID in younger patients described diverse symptoms with fatigue, post-exertional malaise (PEM), and cognitive dysfunction as most frequent requiring a reduced work schedule in almost half and inability to work in 22% of patients. 3 PEM describes an intolerance to mental and physical exertion, which triggers an aggravation of symptoms typically lasting for more than 14 hours up to several days 8 .…”
Section: Introductionmentioning
confidence: 99%
“…weeks (Greenhalgh et al 2020;Ladds et al). The high prevalence of persistent cases indicates that this is not a rare phenomenon and needs to be explored to better control epidemic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of our patients harbored the D614G mutation, which might contribute to its persistence in upper airway samples, such mutation is absent in patients 27 and 29, which belong to B.2.2 lineage. From all Brazilian genomes sequenced so far, more than 96% have this signature, a portion that is much higher than expected for persistent infections (Greenhalgh et al 2020;Ladds et al). Altogether, All rights reserved.…”
Section: Candido Et Al (2020) Showed That Community Transmission Of mentioning
confidence: 97%